GAP-43 expression correlates with spinal motoneuron regeneration following root avulsion - Yuan, Qiuju; Hu, Bing; Su, Huanxing; So, Kwok-Fai; Lin, Zhixiu; Wu, Wutian (Journal of Brachial Plexus and Peripheral Nerve Injury, 2009)
Background The growth-associated protein GAP-43 plays a crucial role in axonal regeneration in injured neurons.Methods We have used immunohistochemistry to investigate the expression of GAP-43 in spinal motoneurons during nerve reconstruction following root avulsion in the neonatal and adult rats.Results Following the injury, GAP-43-immunoreactivity (IR) could be found in adult avulsed motoneurons as early as 1 day, increased from 3 to 7 days and reached a maximal level at 2 weeks post-injury. The up-regulation of GAP-43 in adult avulsed motoneurons was accompanied with the axonal regeneration indicated by numerous regenerating motor axons entering the reimplanted ventral root and nerve. In contrast, GAP-43-IR could not be found in the neonatal avulsed motoneurons at any examined post-injury time points. This failure of up-regulation of GAP-43 was coincident with no axonal regeneration in the reimplanted nerve in the neonatal rats.Conclusion Close association of GAP-43 expression and capacity of regeneration in reimplanted spinal nerve of avulsed motoneurons suggests that GAP-43 is a potential therapeutic target for treatment of root avulsion of brachial plexus.